Comprehensive Analysis of Macrocirculation and Microcirculation in Microgravity During Parabolic Flights - Bimpong-Buta, Nana-Yaw; Muessig, Johanna M.; Knost, Thorben; Masyuk, Maryna; Binneboessel, Stephan; Nia, Amir M.; Kelm, Malte; Jung, Christian (Frontiers in Physiology, 2020)
Background: Knowledge of consequences of acute and long-term effects of microgravity or weightlessness are a prerequisite for manned space missions. So far, influence of microgravity on the circulation along the complete vascular tree including macrocirculation and microcirculation are lacking. Methods: 12 healthy volunteers were subjected to alternating microgravity and hypergravity by parabolic flights. The sublingual microcirculation was assessed by intravital sidestream darkfield microscopy. Furthermore, hemodynamic parameters such as heart rate, blood pressure and cardiac output were recorded by beat-to-beat analysis. Data acquisition was performed in sedentary and in supine postures in normal gravity as well as during phases of microgravity and hypergravity induced by parabolic flight maneuvers. Results: Systolic (median 116 mmHg [102; 129] IQR vs. 125 mmHg [109; 136] IQR, p=0.01) as well as diastolic (median 72 mmHg [61; 79] IQR vs. 80 mmHg [69; 89] IQR, p=0.003) blood pressure was reduced and cardiac output (median 6.9 l/min [6.5; 8.8] IQR vs. 6.8 l/min [6.2; 8.5] IQR, p=0.0002) increased in weightlessness compared to normal gravitation phases in sedentary but not in supine posture. However, microcirculation represented by perfused proportion of vessels and by total vessel density was unaffected in acute weightlessness. Conclusion: Profound changes of the macrocircultion exist in sitting postion, but not in supine position. However, microcirculation remains unaltered in sitting and supine position.